Implementasi Manajemen Metode Qiro’ati dalam Meningkatkan Baca Tulis Al-Qur’an - Eni Rohmawati (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2020)
This study aims to determine the implementation management of the qiro'ati method in an effort to improve reading and writing of the Al-Qur'an. This type of research used qualitative research methods with data collection techniques using observation, interviews and documentation. The results of this study can be concluded that qiro'ati learning activities are carried out for one hour and fifteen minutes, the learning steps start from the line-up stage filled with prayer and memorizing short letters, followed by the teacher giving examples and the children imitating then at the final stage followed by a method of observing and repeating the material that has been presented. From these activities, it is considered capable of improving the reading and writing of the Al-Qur'an TPQ in the Jakenan sub-district, Pati Regency. Supporting and inhibiting factors include implementation, activeness, and infrastructure